(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Nowadays, the need to study and develop the field of linguoculturology, which studies the relationship between language and culture, the manifestation of language in culture and culture in language, is becoming one of the main issues in modern linguistics.This article analyzes the linguistic features of the concept of ugliness in the Uzbek culture.